Orbital Pheochromocytoma Metastasis in 2 Patients With Known Pheochromocytoma. Issue 6 (November 2019) - Rider, Alex J.; Walsh, Anna; Sollenberger, Eric L.; Dryden, Stephen C.; DeAngelis, Kendra D.; Weir, Alva B.; Fowler, Brian T.
Abstract : Two patients with previously diagnosed pheochromocytoma presented with facial pain and ptosis. Imaging revealed orbital lesions. Both patients were referred for surgical evaluation of the orbital mass. Surgical excision was performed for both. Pathology confirmed metastatic pheochromocytoma. Pheochromocytomas commonly metastasize to bone, liver, and other tissues. Five cases of metastasis to orbital bone have been previously described. These 2 cases are unique in that the metastases were not hormonally active, presented soon after initial diagnosis, and were treated palliatively with surgical excision. Previous treatment of orbital bony metastasis used radiotherapy. These cases demonstrate that surgical resection is a viable treatment option in these situations. Orbital metastasis of pheochromocytomas should be considered with the appropriate clinical presentation. These are the first documented cases of intraorbital metastasis, separate from the bony walls. Previously, orbital bony wall metastases were treated with radiation. Surgical excision is a viable option for treatment of such metastases. Orbital involvement should be considered in patients with systemic disease presenting with new ocular findings.